Eye in hand robot arm based automated object grasping system - Ishak, Asnor Juraiza; Nozad Mahmood, Mahmood Sarmad (,International University of Sarajevo, 2019)
The modern robotic systems state that the tracking methodology and the visual servoing are imperative to discover the existence of an object and excite the robot in order to manipulate the target. This paper shows a new object tracking and grasping technique in real time based on Eye in Hand visual servoing structure via a camera mounted at the end of the robot arm. The working principle of the robotic system depends mainly on the prediction based on Kalman filter method that estimates the next location of a moving object in order to specify the path of the target under the scope of the camera. Hereby, the proposed system observes the object and studies its behavior based on the pervious state in order to grasp the target at the exact position. Furthermore, the vision system implements feedback control approach to keep the extracted information of the object updated to solve the stability and the reliability issues that might be encountered. It has to be mentioned that the proposed robotic system was tested by grasping moving objects in different speeds and directions. In addition, the grasping of a stationary object was tested to confirm the practical and the theoretical results. As a final result, it can be stated that the speed of the object is directly proportional with the grasping time and vice versa.